2018
DOI: 10.1101/414268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myh10deficiency leads to defective extracellular matrix remodeling and pulmonary disease

Abstract: Impaired alveolar formation and maintenance are features of many pulmonary diseases that are associated with significant morbidity and mortality. In a forward genetic screen for modulators of mouse lung development, we identified the non-muscle myosin II heavy chain gene, Myh10. Myh10 mutant pups exhibit cyanosis and respiratory distress, and die shortly after birth from differentiation defects in alveolar epithelium and mesenchyme. From omics analyses and follow up studies, we find decreased Thrombospondin ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
(53 reference statements)
1
10
0
1
Order By: Relevance
“…An N-ethyl-N-nitrosourea Mutant Displays Growth Retardation and Goblet Cell Hyperplasia. To identify regulators of early postnatal lung development in mouse, we performed N-ethyl-Nnitrosourea (ENU) mutagenesis (39,40). From screening the F3 progeny of 170 G1 mice, we identified 10 families displaying recessive lung inflammation phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An N-ethyl-N-nitrosourea Mutant Displays Growth Retardation and Goblet Cell Hyperplasia. To identify regulators of early postnatal lung development in mouse, we performed N-ethyl-Nnitrosourea (ENU) mutagenesis (39,40). From screening the F3 progeny of 170 G1 mice, we identified 10 families displaying recessive lung inflammation phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…For RNA sequencing (RNA-Seq), total RNA was isolated from P1 lungs of 2 Ryk +/+ and 2 Ryk SL/SL mice. Whole-exome sequencing and RNA-Seq were performed as previously described (39).…”
Section: Methodsmentioning
confidence: 99%
“…As expected, GO biological process analysis of TNFAIP1-interacting proteins revealed that TNFAIP1 was associated with the cytoskeleton. Among the proteins enriched in these pathways, 6 proteins were involved in cytoskeleton regulation, as shown by analysis of a protein-protein interaction network including FLNB, TLN1, RACGAP1, KIF23, SNX9, and MYH10 [41][42][43][44][45][46][47] . We speculated that BTBD9 affected the expression of these proteins by modulating TNFAIP1 degradation and altering the metastatic ability of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two actin-binding proteins, MYH9 and MYH10, are depleted from the complexes when NSP1 is present. Interestingly, it has been reported that depletion or inactivation of the myosin non-muscle proteins MYH9 and MYH10 leads to renal failure (Otterpohl et al, 2020) or pulmonary disease (Kim et al, 2018), characteristic symptoms of SARS-CoV-2 infection.…”
Section: The Sars-cov-2 5'utr Does Not Bind To Any Component Of the Rmentioning
confidence: 99%